Microbiological Qualities of Red Napier Silage (Pennisetum purpureum cv. Purple) added Prebiotic Inulin - Septian, Mohamad Haris; Sihite, Mikael; Amhar, Radiva Nurya (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
The use of additives in making silage can increase the microbial population and silage quality. One of the prebiotics that can be used is inulin. This study aims to determine the effect and percentage of the best use of inulin probiotics in making red napier grass silage on the microbiological quality of silage. This research was carried out at Kledung Research Park and the Integrated Laboratory of Tidar University. The study method used a Complete Randomized Design (RAL) with four treatments (P0 = Red Napier + 0% inulin), (P1 = Red Napier + 1% Inulin), (P2 = Red Napier + 3% Inulin), (P3 = Red Napier + 5% Inulin) each treatment was repeated 5 times. The data obtained were analyzed using ANOVA and continued using Duncan's Multiple Range Test (DMRT), calculated using IBM SPSS 26 tools. The results of this study showed that the addition of inulin had a real effect (P<0.05) on lactic acid levels and total lactic acid bacteria but no effect (P>0.05) on total bacteria. This study concludes that adding inulin positively impacts lactic acid levels and total lactic acid bacteria silage Red Napier.